The Influence of AI-Based Digital Platforms on The Dynamics of Slang and Social Identity in Social Media - Egatama Arista Damayanti (Prosiding University Research Colloquium, 2026)
This research proposal explores the influence of AI-based digital platforms on the dynamics of slang and social identity in social media. As AI technologies increasingly integrate into social media, they reshape user interactions and language use, profoundly impacting the evolution of slang. Slang serves as a crucial marker of social identity, enabling users to express group affiliations and personal identity. The study aims to analyze how AI features, such as personalized content algorithms and chatbots, affect users' linguistic choices and identity constructions across various social media platforms. Through a mixed-methods approach, combining qualitative and quantitative analyses, this research will contribute to understanding the implications of AI on sociolinguistic dynamics in digital environments.